Analysis of Natural Lighting in Traditional Homes: Pilahuin Case Study - Bustán-Gaona, Darío (2024)
Traditional homes in the Ecuadorian Andean region showcase their culture and tradition in their design. However, they may not be effectively harnessing natural light, making it necessary to analyze this condition. Natural light is essential for creating comfortable and habitable environments in homes. This research aims to understand the influence of natural lighting in traditional homes. On-site measurements and digital simulations were conducted to evaluate the luminous flux in specific areas of these homes. Parameters unique to this type of construction, such as the materials used, orientation, date, and time of day, were considered to ensure the accuracy of the simulations. Using Velux software, it was possible to simulate the sun's trajectory throughout the day and year to comprehend and enhance the luminous performance of these spaces. Measurements and simulations revealed that the levels of illumination in traditional Andean homes fall below the standards established in the Ecuadorian Construction Regulations. This is partly due to the design of small windows on the main facade and the materials used in floors and walls. This demonstrates that integrating natural light into architectural design is crucial for improving the quality of life for occupants and promoting sustainability.